The main sources of molecular organization in the cell. Atlas of self-organized and self-regulated dynamic biostructures - De la Fuente, Ildefonso M.; Cortes, Jesus M.; Malaina, Iker; Pérez-Yarza, Gorka; Martinez, Luis; López, José I.; Fedetz, Maria; Carrasco-Pujante, Jose (Progress in biophysics and molecular biology, 2025)
One of the most important goals of contemporary biology is to understand the principles of the molecular order underlying the complex dynamic architecture of cells. Here, we present an overview of the main driving forces involved in the cellular molecular complexity and in the emergent functional dynamic structures, spanning from the most basic molecular organization levels to the complex emergent integrative systemic behaviors. First, we address the molecular information processing which is essential in many complex fundamental mechanisms such as the epigenetic memory, alternative splicing, regulation of transcriptional system, and the adequate self-regulatory adaptation to the extracellular environment. Next, we approach the biochemical self-organization, which is central to understand the emergency of metabolic rhythms, circadian oscillations, and spatial traveling waves. Such a complex behavior is also fundamental to understand the temporal compartmentalization of the cellular metabolism and the dynamic regulation of many physiological activities. Numerous examples of biochemical self-organization are considered here, which show that practically all the main physiological processes in the cell exhibit this type of dynamic molecular organization. Finally, we focus on the biochemical self-assembly which, at a primary level of organization, is a basic but important mechanism for the order in the cell allowing biomolecules in a disorganized state to form complex aggregates necessary for a plethora of essential structures and physiological functions. In total, more than 500 references have been compiled in this review. Due to these main sources of order, systemic functional structures emerge in the cell, driving the metabolic functionality towards the biological complexity. •The main fundamental principles of molecular organization that shape the Cell.•Biochemical self-organization, regulates the enzymatic oscillatory patterns.•Information processing, the main source of functional and structural complexity.•Self-assembly, at a primary level, fundamental mechanism for molecular order.•Epigenetic marks are controlled by biochemical information processing.